2007
DOI: 10.1097/gco.0b013e3282f1a91b
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus vaccine – more than a vaccine

Abstract: We aim to summarize how updated information, since this debut, can add to our consultations and help give us a collective voice to address the rising healthcare disparities involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Immunogenicity comparisons between males and females were compared via a non-inferiority analysis for each HPV type (6,11,16,18) in the per-protocol populations, including 948, 949, 944 and 952 patients respectively. For each HPV type, ‡99AE5% of patients had seroconverted at month 7, regardless of gender, with males having higher observed GMTs for all vaccine types.…”
Section: LI Ni C a L T R Ial S Dat Amentioning
confidence: 99%
See 2 more Smart Citations
“…Immunogenicity comparisons between males and females were compared via a non-inferiority analysis for each HPV type (6,11,16,18) in the per-protocol populations, including 948, 949, 944 and 952 patients respectively. For each HPV type, ‡99AE5% of patients had seroconverted at month 7, regardless of gender, with males having higher observed GMTs for all vaccine types.…”
Section: LI Ni C a L T R Ial S Dat Amentioning
confidence: 99%
“…It is believed that in addition to providing active protection to young males, protection would be extended to females via herd immunity. This concept may be beneficial in situations of low female vaccination rates (17)(18)(19). While trials have demonstrated a positive immunologic response after quadrivalent HPV vaccine administration in sexually active 11-to 15-year-old boys, conclusive efficacy trials are limited.…”
Section: Safety Datamentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, there are other HPV types, some also considered oncogenic, not covered by the vaccines that also might contribute to these cancers. Likewise, infection with “benign” or low-risk HPVs that cause genital warts have a life-time acquisition risk of 10% in the USA and a worldwide prevalence of 0.6%–3.0%, which also presents major morbidity and economic cost 21,22…”
Section: Introductionmentioning
confidence: 99%
“…Las vacunas profilácticas representan un nuevo instrumentopara prevenir la infección por VPH (14,15). El principio fundamental es la creación de antígenos capaces de inducir anticuerpos neutralizantes que impiden la entrada del virus a la célula huésped.…”
Section: Introductionunclassified